Pengembangan Aplikasi Inventarisasi Peralatan Laboratorium menggunakan Microsoft Access - Agung Samudra; Marko Ayaki Lumbantobing; Muhammad Hudan Rahmat; Sukardi; Wiyogo; Sri Murwantini (Universitas Islam Raden Rahmat, Malang, 2023)
The purpose of inventory is to maintain office infrastructure and facilitate inventory control activities regarding their use. The laboratory of the Mechanical Engineering Education study program, Faculty of Teacher Training and Education, Palangka Raya University has assets in the form of equipment and materials for student practicums. These assets must be managed well so that existing equipment and materials can be controlled properly. Therefore, the aim of this research is to create an equipment inventory application in the form of Microsoft Access. The use of an inventory application in the form of Microsoft Access is expected to make it easier for laboratory heads to control existing equipment and materials. The research method used is the ADDIE R&D model with the following stages: Analysis, Design, Development, Implementation, Evaluation. The results of the research are a laboratory equipment inventory application that has been validated by media experts at 86.66%, material experts at 92.5%, and user response at 88.38% with the conclusion that it is very suitable for use.